The Challenges of Integrating Highly Skilled Migrants into the Professional Sports System - Rajković Iveta, Marijeta (Traditiones, 2023)
Highly skilled migrants in the professional sports system are circular migrants, who migrate repeatedly after each contract change. This article is based on ethnological field research with persons in the sports system (i.e. coaching staff), and analyses the challenges of their integration and well-being. The study shows that migrant sports professionals are not integrated into the host society, but rather into the club and live in a professional “bubble.” Although they are privileged migrants, they often face emotional and social challenges. Each remigration brings new integration challenges, transnational families, “sacrificing” of their spouses’ careers and their children’s social life.